2015
DOI: 10.2144/000114275
|View full text |Cite
|
Sign up to set email alerts
|

Shining a Light on LAMP Assays — A Comparison of LAMP Visualization Methods Including the Novel use of Berberine

Abstract: The need for simple and effective assays for detecting nucleic acids by isothermal amplification reactions has led to a great variety of end point and real-time monitoring methods. Here we tested direct and indirect methods to visualize the amplification of potato spindle tuber viroid (PSTVd) by loop-mediated isothermal amplification (LAMP) and compared features important for one-pot in-field applications. We compared the performance of magnesium pyrophosphate, hydroxynaphthol blue (HNB), calcein, SYBR Green I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
126
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(136 citation statements)
references
References 26 publications
3
126
2
5
Order By: Relevance
“…However, the use of pre-added calcein dye before the amplification process increased in Tt (22 mins) ( Figure 5). Our findings are consistent with a previous study which reported the increased of Tt in real-time fluorescence detection by 10 min when calcein and manganese were used (Fischbach et al 2015). The addition of SYBR Green I and SYBR Safe dyes after the amplification reaction gave positive results in 12 mins at the detection limit 10 3 copies/ μl.…”
Section: Discussionsupporting
confidence: 92%
“…However, the use of pre-added calcein dye before the amplification process increased in Tt (22 mins) ( Figure 5). Our findings are consistent with a previous study which reported the increased of Tt in real-time fluorescence detection by 10 min when calcein and manganese were used (Fischbach et al 2015). The addition of SYBR Green I and SYBR Safe dyes after the amplification reaction gave positive results in 12 mins at the detection limit 10 3 copies/ μl.…”
Section: Discussionsupporting
confidence: 92%
“…A color change is observed aer adding calcein and SYBR Green I to the reaction mixture. 19,20 Hence, these two methods are employed in analysis to avoid the use of carcinogenic ethidium bromide. However, these dyes require equipment for observing illumination which may be an inconvenience for the user.…”
Section: Discussionmentioning
confidence: 99%
“…To name a few, calcein has been used in detection of Trypanosoma cruzi (Besuschio et al 2017), avian influenza H5 virus (Liu et al 2013), hepatitis C virus (Zhao et al 2017), human papillomavirus , human coronavirus (Geng et al 2016) and Flavobacterium columnare in tilapia fish (Suebsing et al 2015). Calcein-based end-point detection is most commonly used due to its high sensitivity and notable colour change for naked eye observation (Fischbach et al 2015).…”
Section: Lamp End-point Detection Methodsmentioning
confidence: 99%